Moderate-intensity exercise alleviates pyroptosis by promoting autophagy in osteoarthritis via the P2X7/AMPK/mTOR axis - Zihao Li (Nature Publishing Group, 2021)
Abstract Instability and excessive use of the knee joint can cause osteoarthritis (OA). Reasonable exercise can enhance the stability of the knee joint and prevent and relieve the occurrence and development of OA. As a key switch for inflammation, P2X purinoceptor 7 (P2X7) has attracted much attention in studies of OA. Exercise can regulate P2X7 expression and activation. However, the role of P2X7 in exercise-based prevention and treatment of OA is unknown. We previously showed that moderate-intensity exercise can significantly alleviate OA symptoms. Accordingly, in this study, we evaluated the effects of exercise on P2X7 expression and activation in chondrocytes. Micro-computed tomography, hematoxylin, and eosin staining, Toluidine Blue O staining, immunohistochemistry, and terminal deoxynucleotidyl transferase dUTP nick-end labeling experiments showed that P2X7 expression was lower in the moderate-intensity exercise group than in the inflammation and low- and high-intensity exercise groups. Additionally, chondrocyte death, cartilage destruction, and the degree and severity of pyroptosis were significantly reduced, whereas autophagy levels were significantly increased in the moderate-intensity exercise group. Cell Counting Kit-8 assay, lactate dehydrogenase release, flow cytometry, enzyme-linked immunosorbent assay, cell fluorescence, western blot, reverse transcription-quantitative polymerase chain reaction, and transmission electron microscopy experiments showed that moderate activation of P2X7 promoted autophagy through the AMP-activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) signaling pathway and promoted autolysosome targeting for degradation of the inflammasome component NLRP3, thereby inhibiting pyroptosis. Additionally, the use of AMPK and mTOR activators and inhibitors indicated that the AMPK-mTOR signaling pathway, as the downstream of P2X7, played a key role in delaying the occurrence and development of OA. We propose that moderate-intensity exercise promoted chondrocyte autophagy through the P2X7/AMPK/mTOR signal axis to alleviate pyroptosis. Our findings provide novel insights into the positive and preventative effects of exercise on OA.